Shooting down trade: Firm-level effects of embargoes - Uğur Aytun; Julian Hinz; Cem Özgüzel (Kiel Institute for the World Economy (IfW Kiel), 2024)
In November 2015, Turkey's unexpected downing of a Russian military jet in Syria prompted Russia to impose a swift and comprehensive embargo on specific Turkish exports. This study leverages this quasi-natural experiment to estimate both the immediate and longer-term effects of the imposition and subsequent lifting of these sanctions. Utilizing administrative data encompassing all Turkish exporters, we first examine the impact on trade at the firm level, assessing the direct effects of the embargo, the redirection of trade to alternative markets, and the circumvention through other products. Second, we investigate broader repercussions on domestic operations, including firms' sales, procurement, and employment. Our findings show that while the embargo caused immediate and substantial declines in exports of affected products to Russia, firms partially mitigated these losses through trade diversion. Although relative trade patterns normalized post-sanctions, absolute trade values remained subdued. The analysis reveals that affected firms experienced declines in domestic sales and supplier relationships, with temporary disruptions in employment. However, most negative effects dissipated following the embargo's removal, except for some persistent reductions in procurement and supplier links. These results contribute to the understanding of sanctions' broader economic implications and the resilience of firms facing trade disruptions.
Keywords: F10; F13; F14; F51; 330; Sanctions; Embargoes; Firm-level Effects; Gravity